2016
DOI: 10.1097/mib.0000000000000735
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Parkinsonʼs Disease and Inflammatory Bowel Disease

Abstract: We suggest that IBD is associated with an increased risk of PD. Patients with IBD should be aware of the potential risk for PD development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
126
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(145 citation statements)
references
References 38 publications
12
126
1
Order By: Relevance
“…2) in both Ashkenazi Jewish and non-Jewish datasets. Intriguingly, a recent independent report has suggested that PD is associated with an increased risk of IBD (34). Taken together, these results point toward potential shared genetic and epidemiological links between these two diseases and can help to identify a subgroup of patients with CD who are at a higher risk for developing PD.…”
Section: Discussionmentioning
confidence: 99%
“…2) in both Ashkenazi Jewish and non-Jewish datasets. Intriguingly, a recent independent report has suggested that PD is associated with an increased risk of IBD (34). Taken together, these results point toward potential shared genetic and epidemiological links between these two diseases and can help to identify a subgroup of patients with CD who are at a higher risk for developing PD.…”
Section: Discussionmentioning
confidence: 99%
“…The LHID 2000 was randomly sampled from the Registry for Beneficiaries and contains original claims data of one million beneficiaries enrolled in 2000. The details of the NHI program and LHID 2000 have been described in previous studies [19, 20]. The diagnoses in the LHID 2000 are coded on the basis of the International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM).…”
Section: Methodsmentioning
confidence: 99%
“…Remarkably, genomewide association studies identified leucine-rich repeat kinase 2 (LRRK2), the most common gene implicated in the pathogenesis of autosomal dominant PD, as one of the susceptibility genes for Crohn's disease [5]. These genetic data have been supported by a recent Taiwanese epidemiological study, which reported an increased risk of PD among individuals with Crohn's disease [6].…”
mentioning
confidence: 92%